Chapter Hou toezicht op de emancipatie! - Senden, Linda (Amsterdam University Press, 2023)
For numerous public interests there are supervisory bodies, such as the Netherlands Authority for the Financial Markets (AFM) and the Netherlands Authority for Consumers and Markets (ACM). Drawing on the multidisciplinary Transformative Equality Approach that was developed in the UU Gender and Diversity Hub, we argue that it is high time to establish a Netherlands Authority for Emancipation (NEMA). Rather than putting the onus for emancipation and equality on those who suffer from inequality, the government should take ownership of inequality problems by establishing a supervisory body for effective compliance and enforcement of equal treatment legislation.